2009
DOI: 10.1038/nnano.2009.141
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of the metal–insulator transition in single-domain vanadium dioxide nanobeams

Abstract: Many strongly correlated electronic materials have a domain structure that greatly influences the bulk properties and obscures the fundamental properties of the homogeneous material. Nanoscale samples, on the other hand, can be smaller than the characteristic domain size, thus making it possible to explore these fundamental properties in detail. Here, we report new aspects of the metal-insulator transition, studied in single-domain vanadium dioxide nanobeams. We have observed supercooling of the metallic phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

28
341
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(373 citation statements)
references
References 28 publications
28
341
4
Order By: Relevance
“…We attribute this remarkably broad hysteresis to an inhibition of the MIT by local strain fields within the embedded clusters or the absence of nucleation sites in small, single-domain VO 2 nanocrystals. This interpretation is fully consistent with recent experiments demonstrating a wide range strain tuning of the MIT critical temperature in single-domain,free-standing VO 2 nanobeams 17,18 . For both diffraction orders of the DS grating [cf.…”
supporting
confidence: 92%
“…We attribute this remarkably broad hysteresis to an inhibition of the MIT by local strain fields within the embedded clusters or the absence of nucleation sites in small, single-domain VO 2 nanocrystals. This interpretation is fully consistent with recent experiments demonstrating a wide range strain tuning of the MIT critical temperature in single-domain,free-standing VO 2 nanobeams 17,18 . For both diffraction orders of the DS grating [cf.…”
supporting
confidence: 92%
“…Over the years, many research groups have invested massive efforts not only to identify the origin of the phase transition in VO2, but also to control the occurrence of the phase transition onset by varying many physical parameters, such as doping, [15,16] strain, [17,18] pulsed voltage, [19,20] and size, [21][22][23] . [15,16] Recently, Whittaker et al reported that the phase transition temperature can be decreased by oxygen vacancy doping, which is induced by reducing VO2 crystal size to nanoscale.…”
mentioning
confidence: 99%
“…[32,33] The optical images of Figure 1d-1e are different from those of VO2 nano-wires or thin films, where the metallic and insulating phases are shown together to coexist during phase transition. [17,18,34] In addition, the heterogeneous phase transition in these crystals occurs from the end surfaces and proceeds with phase boundary motion. [33] This is different from the recent report by Lopez et al, [24] where MIT is initiated by heterogeneous nucleation at extrinsic defect sites within the crystal.…”
mentioning
confidence: 99%
“…Therefore, depending on the precise growth conditions and substrate, an insulating nanobeam can be stabilized in the M1, T, or M2 phase, 41,50 or even in the M1 phase under compressive strain. 51 Substrateinduced strain leads to a striking effect when the nanobeam is subsequently heated back above the transition temperature: quasiperiodic metallic nanodomains form along the nanobeam axis. This phase-coexistence structure persists to temperatures above the normal phase transition region.…”
mentioning
confidence: 99%